Unions and collective bargaining in Australia in 2017. (June 2018) - Gahan, Peter; Pekarek, Andreas; Nicholson, Daniel
In 2017, Australian unions faced ongoing membership decline and new institutional constraints, but emerged reinvigorated from a change in leadership and a policy re-set. Many unions faced a hostile environment for bargaining, with protracted negotiations in key sectors, attended by robust industrial action at times. The decline in union members and collective agreements reached a crisis point. A surprisingly diverse collection of individuals expressed concerns that the system of enterprise bargaining was not producing outcomes that were fair or economically sustainable, with some questioning whether the system had created the level playing field its architects had envisioned, as well expressing growing unease that reforms intended to constrain unions were undermining the original objective of the legislation. Heading into 2018, unions and the Australian Council of Trade Unions were seeking a political and legislative solution to the seemingly entrenched industrial difficulties they face, campaigning around the theme 'change the rules'. Without significant change in the system, it is difficult to see that the coming years will see any change to these dominant patterns.